TURNOVER PADA PT. JASAPOWER INDONESIA - Medy Budun; Muslih Amberi; Emy Rahmawati (Universitas Lambung Mangkurat, 2021)
This research aimed to obtain information about the factors that caused of turnover at PT. Jasapower Indonesia. This study used a descriptive analysis method with a qualitative approach in collecting data using source triangulation techniques through in-depth interviews from a variety of different sources, observation and document review. Informants in the study were consisting of former employees, employees who are still actively working and HRD staff of PT. Jasapower Indonesia. The results showed that turnover intention was motivated by work-family conflict and employee retention at work.Keywords: Work-Family Conflict, Employee Retention, and Turnover Intention